Allocation of water resources in the lower Yellow river based on ecological footprint - Zhang, Shuiling; Li, Hui; Li, Chunhui; Yi, Yujun; Wang, Xuan; Liu, Qiang (Frontiers in Earth Science, 2023)
With the development of the economy, the contradiction of water resources in the lower Yellow River area is becoming increasingly serious. Economic development not only increases the socio-economic water demand, but also causes damage to the environment. In order to ensure the safety of the vast plains along the lower Yellow River, protect the environment of the lower Yellow River and estuaries, and achieve environmental sustainability of the lower Yellow River, a model was established to optimize the allocation of water resources with the goal of ecological, safety, and social benefits, combining the uncertainty of water resources, the uncertainty of the water demand during the flood season under different water and sediment conditions, and the water requirements of different water use units and water departments. An improved ecological footprint method considering soil water was applied during the allocation. Thirty different scenarios were set up, and appropriate scenarios for 2025 and 2030 in wet, normal, and dry years were calculated, providing a reference for decision makers. The results show: 1) The water supply is affected by the amount of water resources and water demand for sediment transport in the lower Yellow River. The satisfaction of sediment transport and the water supply rate during wet years can reach a good level. 2) When the regional water resource ecological footprint is the smallest, the allocation of water resources tends to the unit or sector with a smaller ecological footprint. Therefore, the river sections with the lowest water shortage rates are Lijin-Hekou and Sunkou-Aishan, and the sector with a low water shortage is ecological and industrial water.